Fasting Blood Glucose and Lipid Profile Alterations following Twelve-Month Androgen Deprivation Therapy in Men with Prostate Cancer. (17th October 2012) - Sağlam, Hasan S.; Köse, Osman; Kumsar, Şükrü; Budak, Salih; Adsan, Öztuğ
Abstract : Purpose. In this retrospective study, we aimed to investigate the effects of androgen deprivation therapy (ADT) on blood glucose and blood cholesterol levels over a 12-month period. Materials and Methods. Between January 2010 and June 2012, the data of 44 patients with prostate cancer who were receiving ADT were collected from a hospital database. Patients with additional malignancy or diabetes and those who had been prescribed and were currently taking cholesterol-lowering medication were excluded from the study. Data (including fasting blood glucose levels and a cholesterol profile) were collected and analysed statistically. AP value <0.05 was considered statistically significant. Results. Twelve months after the initiation of ADT, fasting blood glucose (FBG), total cholesterol (TC), low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and triglyceride (TG) levels changed. FBG, TC, LDL cholesterol, and TG increased significantly (P = 0.009, 0.000, 0.000, and 0.000, resp.), while HDL cholesterol decreased (P = 0.000 ). Conclusion. ADT may increase FBG, TC, LDL cholesterol, and TG but decrease HDL cholesterol by the end of a year of treatment. Therefore, close followup may be needed as a consequence of one-year ADT regarding metabolic alterations.